Inflammation: a key mechanism connecting metabolic-associated steatotic liver disease and systemic arterial hypertension - Solleiro-Villavicencio, Helena; Viurcos-Sanabria, Rebeca; Aguayo-Guerrero, José Alfredo; Pineda-Pérez, Pablo Fernando; Méndez-García, Lucía Angélica (Frontiers in Immunology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common chronic liver condition worldwide. The increase in the prevalence of MASLD is linked to the global rise in obesity. MASLD encompasses a disease spectrum beginning with simple steatosis that may progress to metabolic dysfunction-associated steatohepatitis (MASH), cirrhosis, and hepatocarcinoma. Clinical studies highlight the bidirectional relationship between MASLD and systemic arterial hypertension (SAH), showing that MASLD patients have a higher risk of developing SAH. Likewise, hypertensive patients show an increased susceptibility to MASLD, suggesting mutual pathogenic mechanisms. Inflammation is a shared pathway between these two entities; MASLD pathogenesis encompasses hepatic lipotoxicity, inducing the release of pro-inflammatory mediators, which promote systemic inflammation, contributing to vascular remodeling, increased blood pressure, and deregulating the renin-angiotensin system (RAS), potentially contributing to SAH. On the other hand, chronic hypertension promotes hepatic inflammation through immune and neuroendocrine pathways, favoring progression from MASLD to MASH. This review, emphasizing the pro-inflammatory factors, explores the inflammatory crosstalk between MASLD and SAH. Understanding this interplay provides a comprehensive perspective on chronic inflammation that could link liver and vascular pathologies, offering potential therapeutic targets for treating both conditions.